PROXIMATE COMPOSITION AND MICROBIOLOGICAL QUALITY OF FIVE COMMERCIAL BROILER SUPER STARTER FEEDS SOLD IN JOS NORTH LGA OF PLATEAU STATE - Idachaba, C. U.; Abdullahi, I.; Agada, A. I.; Kurdor, P.N. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
The study was conducted to determine the proximate composition and microbiological quality of five selected broiler super starter feeds in Jos North LGA of Plateau State. Five commercial broiler super starter feeds were purchased and designated as samples A, B, C, D and E. A batch of 300g of each feed sample was aseptically collected in plastic bags and analyzed for the proximate composition at the Chemistry Laboratory, Faculty of Natural Sciences, University of Jos. The feed samples were also assayed for microbial contamination (bacteria and fungi) at the Department of Microbiology, Faculty of Natural Sciences, University of Jos. The result of the analysis revealed that percentage crude protein of feed A was highest at 22.49% while feed D had the least crude protein of 18.13%. The metabolizable energy of feeds A, B, C and E were higher than 3000kcal/kg. Feed D was found to fall within the range of 2860-3000kcal/kg recommended for broiler starter chicks. The total plate count ranged from 0.88 to 1.28×105CFU/g, coliform counts ranged between 1.40 to 3.20×104CFU/g, and fungal counts 0.08 to 2.90×105CFU/g. The high coliform count indicated that more attention is needed to improve feed storage practices, warehouse conditions, handling of products and duration of feed storage. The presence of pathogenic microorganisms in poultry feeds is indicative of the level of contamination which could possibly limit growth performance in chickens. Based on the results of this study, it can be concluded that, advocacy for periodic examination of feed nutritional quality and safety to prevent cross contamination of poultry products should be adhered to for profitable poultry production in and around the study area.